Rapid Expression of Human Immunodeficiency Virus following Activation of Latently Infected Cells - Arlen, Philip A. (American Society for Microbiology, 2006)
The host cell activation state impacts the nature of human immunodeficiency virus infection. Activated cells facilitate productive infections; quiescent cells enable the virus to enter a latent state, the major obstacle to viral clearance. We wanted to understand how these differences affected viral gene expression. In quiescent cells activated prior to infection, viral RNA was seen 12 h postinfection; when cells were stimulated postinfection, viral RNA was not seen until 36 h postinfection. Up-regulation of viral RNA in latently infected cells occurred within 2 h poststimulation. This hierarchy also held true for viral protein production. These results may explain the rapid reemergence of viremia following termination of therapy.